The EFFECT OF COMPETENCE AND INDEPENDENCE ON AUDIT QUALITY MODERATED BY AUDITOR WORK EXPERIENCE - Kurniawan, Dadieng; Siagian, Deriska Emiria; Poernamawatie, Fahmi (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2024)
This research is motivated by the existence of audit failure cases which resulted in many auditors and public accounting firms being sanctioned by the Ministry of Finance. The number of cases of audit failure indicates that the quality of audits provided by auditors and public accounting firms is still low. This study aims to determine the effect of Auditor Competence and Independence on Audit Quality with Auditor Work Experience as a moderating variable at the Public Accounting Firm in Malang City. This research uses quantitative methods with a descriptive approach. The types of data used in this study are primary data and secondary data. Data collected by questionnaire technique. The population in this study were 77 auditors who worked at 16 public accounting firms in Malang City who had registered with IAPI in 2023. And the sample in this study were 58 auditors who worked at 10 KAP Malang City. The sampling technique in this study used purposive sampling technique where the sample was determined based on several criteria. Data analysis was performed using the Structural Equation Model (SEM) model with Smart-PLS version 0.4. The results of this study indicate that auditor competence has a positive effect on audit quality. Auditor independence has a positive effect on audit quality. Auditor work experience can strengthen the effect of competence on audit quality. However, auditor work experience cannot strengthen the effect of independence on audit quality.